PENINGKATAN PENGUASAAN KOSAKATA BAHASA INGGRIS SISWA KELAS VI MELALUI TEBAK GAMBAR POHON PADA SDN 030342 SILALAHI, KECAMATAN SILAHISABUNGAN, KABUPATEN DAIRI - Pinta Kesadaran Gea Gea; Betryce Yecisa Br Sitepu; Ristin Ceria Manik; Jolman Tafanao; Ferdinan Natanael Pasaribu; Parsaoran Silalahi (Jurnal Pengabdian Multidisiplin Indonesia (JUPEMI), 2026)
This community service activity aims to improve the English vocabulary mastery of sixth-grade students at SDN 030342 Silalahi through a tree picture guessing game based on the surrounding school environment. The main problems faced by students include the perception that English is a difficult subject due to limited vocabulary, lack of self-confidence, and unvaried teaching methods. The method used in this activity is a community service approach with a contextual learning model based on visual media, involving observation of student activities and evaluation tests to measure understanding before and after the implementation, using a pilot program design conducted in one class consisting of 15 students with an intervention duration of approximately 60 minutes. The implementation of the method is carried out through several stages, namely the preparation stage by identifying student needs, the implementation stage through the delivery of vocabulary material using visual media such as laptops and projectors, and the main activity in the form of a tree picture guessing game based on objects found in the school environment. Furthermore, the evaluation stage is conducted through tests and observation of student participation and engagement during the learning process.